ISOLASI ASAM 3β-HIDROKSI-5-GLUTINEN-28-OAT DARI KULIT BATANG ASAM KANDIS (Garcinia cymosa) DAN AKTIVITAS SITOTOKSIKNYA TERHADAP SEL KANKER PAYUDARA MCF-7 - Darwati, Darwati; Khairunnisa, Shofiyah; Nurlelasari, Nurlelasari; Herlina, Tati; Supratman, Unang; Hanafi, Muhammad (BRIN Publishing, 2024)
The Garcinia genus comes from the Clusiaceae family which grows a lot in the tropical forests of Indonesia. This genus is reported to contain many secondary metabolites, one of which is triterpenoid which is useful as a cytotoxic, anti-oxidant, anti-inflammatory, anti-HIV, and antibacterial. One species of Garcinia whose triterpenoid content is still not widely known is G. cymosa. This study aims to obtain triterpenoid compounds in G. cymosa stem bark that are active against MCF-7 breast cancer cells. G. cymosa stem bark powder (0.9 kg) was macerated in stages with n-hexane and ethyl acetate as solvents. The ethyl acetate extract showed positive results for containing triterpenoid compounds after being tested with the Liebermann-Burchard reagent, so the ethyl acetate extract (25 g) was purified and purified by various chromatographic methods. The chemical structure of pure isolate (10 mg) was determined using various spectroscopic techniques IR, MS, 1H-NMR, 13C-NMR, 1H-1HCOSY, HMQC, and HMBC and compared with the literature so that it was designated as triterpenoid acid 3β-hydroxy-5- gluten-28-oat and required its cytotoxic activity using the Presto Blue method against MCF-7 breast cancer cells with an IC50 value of 94.78 µg/mL. This IC50 value belongs to the active category so this compound has potential as an anticancer drug.